Factors influencing the church's financial management (A case study of the gospel church in Timor (GMIT) Paulus Taekiu Klasis Soe Timur) - Jibrael Boimau; Rolland E. Fanggidae; Wehelmina M. Ndoen (LPPM STIE KRAKATAU, 2025)
Purpose: This study aims to determine the factors that influence the financial management of the Paulus Taekiu church. Research methodology: To apply this purpose, the type of data used in this study is qualitative data, while the data sources in this study are primary and secondary data. The data analysis technique used is interactive analysis. Results: The research conducted can be found that in the financial management of the Paulus Taekiu church, there is planning, direction, organization, and financial supervision but the financial management performance is inconsistent because of the factors that affect the financial management of the Paulus Taekiu church, namely the lack of understanding of human resources, the provision of inadequate support facilities, and changes to the GMIT treasury management system.